Differences in the pre‐hospital management of women and men with stroke by emergency medical services in New South Wales. Issue 3 (13th July 2022) - Wang, Xia; Carcel, Cheryl; Hsu, Benjumin; Shajahan, Sultana; Miller, Matthew; Peters, Sanne; Randall, Deborah A; Havard, Alys; Redfern, Julie; Anderson, Craig S; Jorm, Louisa; Woodward, Mark
Abstract: Objectives: To examine whether pre‐hospital emergency medical service care differs for women and men subsequently admitted to hospital with stroke. Design, setting, participants: Population‐based cohort study; analysis of linked Admitted Patient Data Collection and NSW Ambulance data for people admitted to New South Wales hospitals with a principal diagnosis of stroke at separation, 1 July 2005 – 31 December 2018. Main outcome measures: Emergency medical service assessments, protocols, and management for patients subsequently diagnosed with stroke, by sex. Results: Of 202 231 people hospitalised with stroke (mean age, 73 [SD, 14] years; 98 599 women [51.0%]), 101 357 were conveyed to hospital by ambulance (50.1%). A larger proportion of women than men travelled by ambulance (52.4% v 47.9%; odds ratio [OR], 1.09; 95% CI, 1.07–1.11), but time between the emergency call and emergency department admission was similar for both sexes. The likelihood of being assessed as having a stroke (adjusted OR [aOR], 0.97; 95% CI, 0.93–1.01) or subarachnoid haemorrhage (aOR, 1.22; 95% CI, 0.73–2.03) was similar for women and men, but women under 70 years of age were less likely than men to be assessed as having a stroke (aOR, 0.89; 95% CI, 0.82–0.97). Women were more likely than men to be assessed by paramedics as having migraine, other headache, anxiety, unconsciousness, hypertension, or nausea. Women were less likely than men to be managed according to the NSW Ambulance pre‐hospital stroke care protocol (aOR, 0.95; 95% CI, 0.92–0.97), but the likelihood of basic pre‐hospital care was similar for both sexes (aOR, 1.01; 95% CI, 0.99–1.04). Conclusion: Our large population‐based study identified sex differences in pre‐hospital management by emergency medical services of women and men admitted to hospital with stroke. Paramedics should receive training that improves the recognition of stroke symptoms in women.